2016
DOI: 10.1091/mbc.e15-05-0260
|View full text |Cite
|
Sign up to set email alerts
|

Microhomology-mediated end joining is the principal mediator of double-strand break repair during mitochondrial DNA lesions

Abstract: Repair of double-strand breaks in mammalian mitochondria depends on microhomology-mediated end joining (MMEJ). Classical NHEJ is not detectable in mitochondria. DNA ligase III, but not ligase IV or ligase I, is involved in mitochondrial MMEJ. The protein machinery involved in miitochondrial MMEJ includes CtIP, FEN1, ligase III, MRE11, and PARP1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 84 publications
(110 reference statements)
6
135
0
2
Order By: Relevance
“…Previous studies have suggested that different cancer cells have varying levels of c‐NHEJ . Although it was correlated with differential expression of NHEJ proteins, levels of BCL2 expression were also responsible as it can interact with KU proteins . Observed robust expression of BCL2 in SUDHL8, further support our finding of weak c‐NHEJ in SUDHL8 cells (data not shown).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Previous studies have suggested that different cancer cells have varying levels of c‐NHEJ . Although it was correlated with differential expression of NHEJ proteins, levels of BCL2 expression were also responsible as it can interact with KU proteins . Observed robust expression of BCL2 in SUDHL8, further support our finding of weak c‐NHEJ in SUDHL8 cells (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, background recombination due to bacterial proteins is subtracted from recombination catalyzed by DLBCL extracts in every experiment. Besides, previously such biochemical assay systems have been used extensively to assess HR mediated repair in human and other mammalian cells . Thus, it appears that HR mediated DSB repair is operational to maintain the integrity of the genome in cell cycle stages when the homologous chromosome partner is available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA Ligase IV/XRCC4 along with XLF and PAXX help in final ligation of DNA ends . In case of MMEJ, Ligase III and/or Ligase I along with other proteins help in repair of DSBs, whereas during HR, the Ligase involved is Ligase I [].…”
Section: Introductionmentioning
confidence: 99%